Risk Factors and Prognosis in Patients With Anti-N-Methyl-D-Aspartate Receptor Encephalitis Requiring Prolonged Mechanical Ventilation - Lin, Jingfang; Xiang, Qu; Liu, Xu; Li, Jinmei (Frontiers in Neurology, 2022)
Background: Mechanical ventilation (MV) is being commonly used in anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis patients with serious conditions. However, little is known about the potential risk factors and long-term outcomes of anti-NMDAR encephalitis requiring MV, especially prolonged MV. Methods: The data collected prospectively from 305 patients with anti-NMDAR encephalitis was retrospectively reviewed. The functional outcome was assessed using modified Rankin scale (mRS) every 3 months. Results: We identified 62 (20.3%) patients required MV. The most common reasons for MV were decreased consciousness and/or status epilepticus. Among 60 patients analyzed, 27 patients requiring prolonged MV (> 15 days). Prolonged MV primarily was based on the younger age, coma, tumor and severe pneumonia. During the follow-up (median: 28 months, range: 3-87 months), 77% of patients requiring MV exhibited a good outcome. In univariate analysis, prolonged MV, higher levels of C-reactive protein and neutrophil-to-lymphocyte ratio were found to be associated with poor neurological outcome at 6 months. Although the prolonged MV group exhibited a longer time to achieve good outcome as compared to the short MV group (median duration 6 months vs 3 months, p = 0.004), no significance difference was observed between the two groups about long-term outcome. Conclusions: It is important to recognize that most anti-NMDAR encephalitis patients requiring MV will achieve favorable long-term outcome, despite the longer duration of MV. Our results may help clinicians in the ventilator management of severe anti-NMDAR encephalitis patients.